Translating Home in the Global South (Taylor & Francis, 2024)
This collection explores the relationships between acts of translation and the movement of peoples across linguistic, cultural, and physical borders, centering the voices of migrant writers and translators in literatures and language cultures of the Global South. To offer a counterpoint to existing scholarship, this book examines translation practices as forms of both home-building and un-homing for communities in migration. Drawing on scholarship from translation studies as well as eco-criticism, decolonial thought, and gender studies, the book’s three parts critically reflect on different dimensions of the intersection of translation and migration in a diverse range of literary genres and media. Part I looks at self-translation, collaboration, and cocreation as modes of expression born out of displacement and exile. Part II considers radical strategies of literary translation and the threats and opportunities they bring in situations of detention and border policing. Part III looks ahead to the ways in which translation can act as a powerful means of fostering responsibility, solidarity, and community in building an inclusive, multilingual public sphere even in the face of climate crisis. This dynamic volume will be of particular interest to students and scholars in translation studies, migration and mobility studies, postcolonial studies, and comparative literature.